f(x)=2/3x−1 and g(x)=−4x+6. What transformation occurs from function f to function g?

A) a vertical translation 6 uni

Question

f(x)=2/3x−1 and g(x)=−4x+6. What transformation occurs from function f to function g?

A) a vertical translation 6 units down

B) a horizontal compression by a factor of −6

C) a horizontal stretch by a factor of −6

D) a horizontal translation 6 units left

in progress 0
Kaylee 4 months 2021-08-01T11:14:52+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-01T11:16:02+00:00

    Step-by-step explanation:

    g(x) = 4x + 6 =0

    x= -6/4

    f(-6/4) = 2 – 1 = 2× 4 – 1 = 8 18

    6 18. 18.

    4

    = 26

    18

    = 13 Ans

    6

    = (c) is correct

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )